Analysis of Coronary Angiography and Revascularization Rates Made Over 5 Years in Public Institutions in Türkiye - Attila Beştemir; Ziya Apaydın; Ali Yaşar Kılınç (Anatolian Journal of Cardiology, 2023)
Background: Coronary angiography is currently the gold standard anatomic imaging method used to diagnose obstructive epicardial coronary artery disease. In patients with critical coronary stenosis, surgical or percutaneous revascularization is provided. Normal coronary artery ratio in coronary angiography is an indirect indicator of patient selection quality. The aim of our study is to evaluate the efficiency of coronary angiography by examining the revascularization rates according to years in patients who underwent coronary angiography.